Addressing accessibility issues in the vicinity of selected MRT-3 Stations based on the needs of the vulnerable population through Universal Design Principles - Corpuz, Daphne G. (College of Architecture, University of the Philippines Diliman, 2023)
Public transportation systems play a crucial role in providing efficient transportation options for people. However, accessibility challenges persist in many public transportation services, particularly in Metro Manila, Philippines. The vulnerable population including the pregnant, elderly, and people with disabilities (PWDs) have mobility considerations that are necessary to be addressed. This study focuses on assessing the accessibility of the immediate environment surrounding Shaw Blvd., Ayala, and Taft Avenue stations of the MRT-3 based on the needs of the vulnerable population. The study aims to investigate the experiences of the vulnerable population who use the MRT-3 and identify areas for improvement in the pedestrian infrastructure surrounding the stations to enhance accessibility. A critical component of this study is conducting surveys with the vulnerable population who use the selected stations to identify the accessibility issues they encounter, the level of difficulty they face in accessing the stations, and the impact of accessibility issues on their physical and psychological well-being. An objective assessment on the immediate environment of the selected MRT-3 stations is also conducted using checklists based on the guidelines outlined in the Accessibility Law. The study proposes recommendations for enhancing the immediate environment of the selected MRT-3 stations, with consideration to the needs of the vulnerable population. These recommendations are guided by Universal Design Principles, and they comply with the Accessibility Law of the Philippines. Through the study, the Metro Manila Development Authority will recognize the need to strictly implement the guidelines that highlight the needs of the vulnerable population. It can also be used as a basis for assessing the accessibility of the immediate environments of other railway systems in the Philippines.